An unprecedented spiro [furan-2, 1'-indene]-3-one derivative and other nematicidal and antimicrobial metabolites from Sanghuangporus sp. (Hymenochaetaceae, Basidiomycota) collected in Kenya. (June 2018) - Chepkirui, Clara; Cheng, Tian; Matasyoh, Josphat; Decock, Cony; Stadler, Marc
Graphical abstract: Highlights: An unprecedented and six known metabolites were isolated from a Kenyan basidiomycete. The fungus belongs to " Inonotus linteus complex" of medicinal mushrooms. Some of the compounds exhibited moderate antimicrobial and nematicidal activities. Abstract: Bioassay guided fractionation of extracts derived from submerged cultures of a Sanghuangporus sp. (i.e., the genus that was until recently referred to as the " Inonotus linteus complex" of medicinal mushrooms) originating from Kenya led to the isolation of a new spiro [furan-2, 1'-indine]-3-one derivative, for which we propose the trivial name phelligridin L (1 ) together with the known compounds 3, 14′-bihispidinyl (2 ), hispidin (3 ), ionylideneacetic acid (4 ), 1 S -(2 E )-5-[(1 R )-2, 2-dimethyl-6-methylidenecyclohexyl]-3-methylpent-2-enoic acid (5 ), phellidine E (6 ) and phellidine D (7 ). Compounds1 –3, showed moderate nematicidal activity against Caenorhabditis elegans with LD50 of 12.5 μg/m. The nematicidal activity of 3, 14′-bihispidinyl and hispidin (1, 2 ) has not been reported before. Furthermore, compounds1 –5 demonstrated moderate antimicrobial activity against various test organisms.